Anisotropic selective etching between SiGe and Si. (22nd May 2018) - Ishii, Yohei; Scott-McCabe, Ritchie; Yu, Alex; Okuma, Kazumasa; Maeda, Kenji; Sebastian, Joseph; Manos, Jim
Abstract: In Si/SiGe dual-channel FinFETs, it is necessary to simultaneously control the etched amounts of SiGe and Si. However, the SiGe etch rate is higher than the Si etch rate in not only halogen plasmas but also physical sputtering. In this study, we found that hydrogen plasma selectively etches Si over SiGe. The result shows that the selectivity of Si over SiGe can be up to 38 with increasing Ge concentration in SiGe. Attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) results indicate that hydrogen selectively bonds with Si rather than with Ge in SiGe. During the etching, hydrogen-induced Si surface segregation is also observed. It is also observed that the difference in etched amount between SiGe and Si can be controlled from positive to negative values even in Si/SiGe dual-channel fin patterning while maintaining the vertical profiles. Furthermore, no plasma-induced lattice damage was observed by transmission electron microscopy for both Si and SiGe fin sidewalls.